2023
DOI: 10.1038/s41562-023-01543-7
|View full text |Cite
|
Sign up to set email alerts
|

Human generalization of internal representations through prototype learning with goal-directed attention

Abstract: Latent causes that give rise to experience are encountered in complex, high-dimensional feature spaces.How then do people approximate the external world with lower-dimensional internal representations that generalize to novel examples or contexts? Theories suggest internal representations could be determined by discriminative boundaries, or based on the distance from prototypes/exemplars. We developed theoretical models that use both discriminative and prototype/exemplar components to form internal representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 78 publications
(68 reference statements)
1
12
1
Order By: Relevance
“…We found that the majority of participants were fit best by the prototype model, even after paired-associate learning. The dominance of the prototype strategy in this task is consistent with prior work Bowman & Zeithamova, 2018Pettine et al, 2023), here being extended to a situation when the same category structure is learned incidentally. Nevertheless, we also observed a trend towards more reliance on exemplars following paired-associate learning when directly comparing the proportions of exemplarists and prototypists across groups.…”
Section: Discussionsupporting
confidence: 85%
“…We found that the majority of participants were fit best by the prototype model, even after paired-associate learning. The dominance of the prototype strategy in this task is consistent with prior work Bowman & Zeithamova, 2018Pettine et al, 2023), here being extended to a situation when the same category structure is learned incidentally. Nevertheless, we also observed a trend towards more reliance on exemplars following paired-associate learning when directly comparing the proportions of exemplarists and prototypists across groups.…”
Section: Discussionsupporting
confidence: 85%
“…Hybrid Concept Learning Using Bayesian Principles. Today, the most prolific theories of concept learning are considered hybrids and have a duality of both rule-and similaritybased interpretations (Pettine et al 2023). One influential example is the Bayesian concept learning framework (Figure 1d; Tenenbaum & Griffiths 2001), which uses a distribution over hypothesized category boundaries (boxes in Figure 1d) to categorize novel stimuli (Sidebar 2.1).…”
Section: Concept Learningmentioning
confidence: 99%
“…Subjects performed a Context Generalization task that identifies qualitatively unique strategies related to goal-directed attention, learning and short-term memory (Pettine et al, 2023). In the task, subjects encountered a visual stimulus defined by color, shape, texture and size.…”
Section: Task Structurementioning
confidence: 99%
“…Importantly, locations in feature space were associated with unique patters of actions and error (Fig. S2) that reflected distinct cognitive strategies (Pettine et al, 2023).…”
Section: Task Structurementioning
confidence: 99%
See 1 more Smart Citation